An isothermal adjustment to nucleation in supersonic flows. (June 2023) - Vallet, David; Pang, Tao; Chen, Yi-Tung; Morris, Melissa
Abstract: The theory of classical nucleation in supersonic flows through a converging–diverging nozzle is examined through quasi-one-dimensional simulations. We propose a new correction to the nucleation rate that accounts for non-isothermal effects. A droplet growth rate derived from Hill's energy equation and combined with the continuum droplet growth rate is included for the application of condensation in both high and low Knudsen number flows. We demonstrate the effectiveness of our model in predicting the onset of nucleation and the associated pressure rise by consider both low pressure ( ≈ 40 kPa) and high pressure ( ≈ 10 MPa) flows of supersonic steam and find improvement in the agreement with experimental data that is driven by the improved isothermal correction. Highlights: A quasi one dimensional simulation capable of capturing condensation shocks. Modelling spontaneous nucleation in high and low pressure supersonic flows for H2 O. The non-isothermal correction for classical nucleation is adjusted for more accurate results. Droplet radius and pressure ratio calculations in nucleating supersonic flows. Subsonic to supersonic flow through converging–diverging, de Laval nozzles.